Let's begin by listing out the given information:
![\begin{gathered} f\mleft(x\mright)=3^x+3\Rightarrow y=3^x+3 \\ Switch\text{ }the\text{ }variables\text{ x \& y in the equation, we have:} \\ x=3^y+3\Rightarrow x-3=3^y \\ x-3=3^y\Rightarrow3^y=x-3 \\ \text{Take the }ln\text{ }o\text{f both }sides\text{, we have:} \\ y=(ln(\left(x - 3 \right)))/(ln(\left(3 \right))) \\ y=f^(-1)\mleft(x\mright) \\ f^(-1)\mleft(x\mright)=(ln((x-3)))/(ln((3))) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/851u5dzcqnosom62fq9d0wyyu9aulphtz3.png)
2.
The domain of a function is the set of input or argument values for which the function is real and defined. This is given by:
![\begin{gathered} x-3;x>3 \\ \therefore x>3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ntrd5uj0ltashwj2pojhulnahzq55bwg5x.png)
3.
The range of a function is the set of output values for which the function is defined. This is given by:
![\begin{gathered} 3^x+3\colon-\infty\: <strong>4. </strong><p>The range of f(x) is the domain of f^-1(x) since they are inverse of one another. </p>[tex]\begin{gathered} f\mleft(x\mright)=3^x+3 \\ x=0 \\ f(0)=3^0+3=1+3=4 \\ x=1 \\ f(1)=3^1+3=3+3=6 \\ x=2 \\ f(2)=3^2+3=9+3=12 \\ \end{gathered}]()
Therefore, the domain of f^-1(x) increases
5.
The asymptote of a curve is a line such that the distance between the curve and the line approaches zero
![\begin{gathered} \: (\ln\left(x-3\right))/(\ln\left(3\right))\colon\quad \mathrm{Vertical}\colon\: x=3 \\ \therefore x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/49xkbqas9se2yl5dqf0iuxfudghsxjetqi.png)